(untitled) (Fiep Bulletin - online, 2014)
When we watch the television programs known as "reality shows," we can observe a salient element, namely, the notion of an existing game. It is our intention to explore both: the conceptions of game in such programs and the understanding of this conception by the viewers. We have opted for the study of ’Big Brother Brasil’, broadcast by Globo Television Network. The data was collected in semi-structured interviews and closed-question questionnaires with groups of viewers with similar characteristics. The analysis and interpretation of data, achieved with qualitative and quantitative methods, tends to indicate that the programs disseminate a conception of a game that subverts hegemonic ethical and moral values in Brasil.